POLICIES ON INDONESIAN IDENTITY IN THE DIGITAL AGE: STUDENT AWARENESS OF GENDER DISCRIMINATION - Mechelle Juana Chandra; Dea Fatmawati; Evita Fairuza Salsabila; Moh. Ayub Alchabib; Moses Glorino Rumambo Pandin (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Indonesia is full of diversity. Therefore, it is necessary to inculcate the value of tolerance considering that the social conditions of the multicultural society have the impact of discriminatory actions, one of which is gender discrimination. This study aims to determine the condition of students' awareness of gender discrimination in the digital era and what actions are appropriate to respond to this level of awareness. This study uses a qualitative research method with an instrument in the form of a questionnaire so that the results of data collection can be discussed in order to find conclusions about answers to the questions that have been mentioned. The results showed that the average knowledge of students about gender discrimination was not that far away and most students still found gender discrimination in their surrounding environment but had never experienced it.